Revision of the European Delia pruinosa species group (Diptera: Anthomyiidae) feeding as larvae in seed capsules of Silene L. (Caryophyllaceae) - Michelsen, Verner (Zootaxa, 2012)
The European taxon Delia pruinosa (Zetterstedt) currently treated as one species is shown to represent a complex of several closely related species all characterized by the short antennnae, enlarged proboscis with strong, black prestomal teeth and a weak tibial setation. Biologically, all members of this Delia pruinosa species group may share the larval habit of living in seed capsules of various species of Silene L. (Caryophyllaceae). The number of species recognized in both sexes is presently raized from one to four: Delia pruinosa (Zetterstedt, 1845), D. judicariae (Pokorny, 1893), D. sileni sp. nov. and D. capdellae sp. nov. It is further documented that a few more species exist within this species group, but they are so far only known from female individuals. The known distribution of the Delia pruinosa species group includes Europe and western Anatolia.